The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.brs.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Stimulation of Prefrontal Cortex Strengthens Existing Episodic Memories and Reduces Forgetting in the Elderly

Abstract: Memory consolidation is a dynamic process. Reactivation of consolidated memories by a reminder triggers reconsolidation, a time-limited period during which existing memories can be modified (i.e., weakened or strengthened). Episodic memory refers to our ability to recall specific past events about what happened, including where and when. Difficulties in this form of long-term memory commonly occur in healthy aging. Because episodic memory is critical for daily life functioning, the development of effective int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 70 publications
(99 reference statements)
1
27
1
5
Order By: Relevance
“…A noninvasive brain stimulation technique that can be used to modulate memory in physiological aging is transcranial Direct Current Stimulation (tDCS) [5,6]. TDCS has been used for two main purposes in memory research: (1) to test the causal relationship between activity of a cortical region and a memory function; and (2) to investigate whether tDCS might modulate memory formation and learning, an issue of relevance for research and neurorehabilitation [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A noninvasive brain stimulation technique that can be used to modulate memory in physiological aging is transcranial Direct Current Stimulation (tDCS) [5,6]. TDCS has been used for two main purposes in memory research: (1) to test the causal relationship between activity of a cortical region and a memory function; and (2) to investigate whether tDCS might modulate memory formation and learning, an issue of relevance for research and neurorehabilitation [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…tDCS studies have shown that the left lateral prefrontal cortex (PFC) contributes to verbal episodic memories along the life span [8][9][10][11][12][13] and enhancement of these abilities has been reported in healthy older adults after the application of tDCS over this brain area [8,9,13]. Specifically, Sandrini and coworkers [8,9] showed that anodal tDCS strengthened memories when applied during the encoding phase or after the consolidation process in elderly individuals. However, an aspect that has not been directly investigated in previous studies is the optimal timing of stimulation to induce long-lasting positive effects on episodic memory function.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations